O ensino de Geografia e a Educação Ambiental (E.A.): uma proposta de aplicação no ensino no Bairro da Terra Firme – Belém – PA - SANTOS, Andreisson da Conceição (2023)
The present study focuses on the presenter the relationship between the Teaching of Geography and Environmental Education (E.A.). Our main objective is a teaching proposal that presents a link between Geography and the teaching themes of E.A. Initially, we make a brief contextualization of the relationship between society and nature and its evolution in the distance and differentiation between environment and society, especially when observed under the capitalist logic. In the second part, we conceptualize Environmental Education according to the legal parameters and the understanding of the authors in the area. Subsequently, we present a relationship that could be established between the Geography Teacher and the E.A. in practice, we have re-established the history of the evolution of geographic science and the teaching of the teacher's geographical orientation, to enable the debate of teaching topics.A. Finally, we present a methodological proposal that links geographic themes and environmental education. We used as a teaching methodology the pedagogical practice reality in the state public network. With the accomplishment of the practice it was possible to establish the link between the Teaching of Geography and the Environmental Education in the Teaching Practice.